Kompetensi Kepribadian Guru PAI Dalam Meningkatkan Interaksi Pembelajaran Peserta Didik di SMP Integral Rahmatullah Toli-Toli - Andi Muhammad Abrar (Formosa Journal of Social Sciences (FJSS), 2022)
This study aims to determine the competence of Islamic religious education (PAI) teachers in improving learning interactions at SMP Integral Rahmatullah Tolitoli. This research uses descriptive qualitative research methods, through observation and in-depth interviews and documentation studies. The data obtained were analyzed using data reduction techniques, data presentation, data verification, and drawing conclusions. The results showed that: 1. PAI teachers have Personality Competencies in the form of: Steady and stable teacher personality, mature teacher personality, wise teacher personality, authoritative teacher personality, personality and teacher who have noble character and can be an example. 2. Efforts by PAI teachers to increase learning interactions, namely, first, teacher interaction with students. Second, interaction between students and teachers through dialogue about problems that have not been understood from the teacher's explanation.